2014
DOI: 10.1016/j.devcel.2014.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Bound Methyltransferase Complex VapA-VipC-VapB Guides Epigenetic Control of Fungal Development

Abstract: Epigenetic and transcriptional control of gene expression must be coordinated in response to external signals to promote alternative multicellular developmental programs. The membrane-associated trimeric complex VapA-VipC-VapB controls a signal transduction pathway for fungal differentiation. The VipC-VapB methyltransferases are tethered to the membrane by the FYVE-like zinc finger protein VapA, allowing the nuclear VelB-VeA-LaeA complex to activate transcription for sexual development. Once the release from V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 43 publications
4
84
0
Order By: Relevance
“…Most studies on veA have been carried out in Aspergillus spp., where this gene has been described to control photodependent development, secondary metabolism and pathogenesis-associated processes [14][16]. Thorough genetic, molecular, and biochemical work has recently shown that Velvet is part of a high-molecular-weight complex containing at least 10 different proteins, some of which have been assigned distinct regulatory roles [15], [22][26]. The VeA orthologue VEL1 of Trichoderma virens has been shown to regulate sporulation, chlamydospore formation, secondary metabolite synthesis and mycoparasitism [27].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on veA have been carried out in Aspergillus spp., where this gene has been described to control photodependent development, secondary metabolism and pathogenesis-associated processes [14][16]. Thorough genetic, molecular, and biochemical work has recently shown that Velvet is part of a high-molecular-weight complex containing at least 10 different proteins, some of which have been assigned distinct regulatory roles [15], [22][26]. The VeA orthologue VEL1 of Trichoderma virens has been shown to regulate sporulation, chlamydospore formation, secondary metabolite synthesis and mycoparasitism [27].…”
Section: Introductionmentioning
confidence: 99%
“…Release to the nucleus depends on environmental conditions where asexual development is favored. Nuclear VipC-VapB reduces negative histone tags and promotes asexual development (377).…”
Section: Fruiting Body Formationmentioning
confidence: 99%
“…Because recent reports from other euascomycetes point to a functional link between VeA homologs and several putative MTases (40 42), we focused further analyses on this group of new PcVelA target genes. First, we performed quantitative reverse transcription-PCR (qRT-PCR) analysis to validate the PcVelA-dependent expression of MTase-encoding genes.…”
Section: Resultsmentioning
confidence: 99%
“…Pc18g06010 showed PcVelA-dependent expression in qRT-PCR but not in microarray analysis (Table 2). Next, the amino acid sequences of the putative MTases were compared to the sequences of PcLaeA, a putative methyltransferase that is part of the velvet complex, as well as A. nidulans LlmF, VapB, and VipC (homolog of PcLlmB), which have previously been described as velvet-associated proteins (40, 41). In general, a set of three conserved sequence motifs (motifs I to III) that are essential for catalytic activity are found in most MTases (43, 44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation